ANALYSIS OF FIXED WIRELESS ACCESS MOBILE SERVICE ON TIGHT COMPETITION IN INDONESIAN TELECOMMUNICATION INDUSTRY - Hapsoro, Anggit Tri; Ichsan, Mohammad (Journal of Business Strategy and Execution, 2013)
Nowadays, with the increasingly competitive business in Indonesian telecommunication industry, every telecommunication operator required to have good business strategies to have an edge over the competition and have a good market share in the competition. The study covered to analyze the competition between Brand ABC with other CDMA and GSM operators in Indonesian telecommunication industry. This analysis is to compare several categories from the aspects of technology, regulation, product & service, and marketing strategy based on the data obtained from related companies about Brand ABC and competitors. Brand ABC is FWA mobile service from PT XYZ which has the objective to facilitate the communication for Indonesian people. The main focus and the methodology of this Thesis are to gather all information about Brand ABC at telecommunication operator PT XYZ. The methodology of case study that used in this Thesis are field research and desk research. Field research is interview with related group at PT XYZ and Desk Research is data collecting method from several books, published report, online journals. Further more, the objective of this Thesis are to understand how to choose the strategy and differentiate for Brand ABC, and also to improve the strategy of new product implementation in the future.Finally, it concluded that the Brand ABC has some strengths and weaknesses in terms of â€œTechnologyâ€, â€œRegulationâ€, â€œProduct and Servicesâ€, and â€œMarketing Strategyâ€. Based on the data, the company should be able to avoid those weaknesses by optimize its strengths.